Acute Renal Dysfunction After Cardiac Surgery: Predictors, Mechanisms of Development and Criteria for Diagnosis - Yu. V. Belov; P. F. Litvitsky; I. A. Vinokurov (Сеченовский вестник)
This publication describes severe complication after cardiac surgery – acute renal failure; the current literature on the development of acute renal failure after cardiac surgery. In publication report reason of acute renal failure, the criteria for diagnosis are viewed. The criteria for diagnosis are discussed, taking into account the specifi cs of kidney damage after cardiopulmonary bypass or a long period of ischemia. The article describes methods of reducing kidney damage during cardiac arrest during thoracoabdominal aorta surgery. The information is presented in terms of the clinician, they can be applied in everyday practice of the surgeon. Accounting data presented will reduce the incidence of this complication.